2008
DOI: 10.1529/biophysj.107.115980
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Dependence of Charge Transport through DNA Revealed by Silicon-Based Nanotweezers Manipulation

Abstract: The study of the electrical properties of DNA has aroused increasing interest since the last decade. So far, controversial arguments have been put forward to explain the electrical charge transport through DNA. Our experiments on DNA bundles manipulated with silicon-based actuated tweezers demonstrate undoubtedly that humidity is the main factor affecting the electrical conduction in DNA. We explain the quasi-Ohmic behavior of DNA and the exponential dependence of its conductivity with relative humidity from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 49 publications
5
78
1
1
Order By: Relevance
“…In recent years, studies examining the electrical properties of double-helical DNA and DNA bundles have found a similar dependence of conductivity on relative humidity [7,8,9]. Experimental data shows that the conductivity of DNA increases by a simple exponential over nearly the entire range of relative humidity (10% to 100%), and spans roughly six orders of magnitude.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, studies examining the electrical properties of double-helical DNA and DNA bundles have found a similar dependence of conductivity on relative humidity [7,8,9]. Experimental data shows that the conductivity of DNA increases by a simple exponential over nearly the entire range of relative humidity (10% to 100%), and spans roughly six orders of magnitude.…”
Section: Introductionmentioning
confidence: 97%
“…Most biomacromolecules were extensively characterized in aqueous environments, but in TLC phases, their solvent-free properties and functions could be investigated in a state in which no or only traces of water are present. Water exhibits a high dielectric constant and has the ability to form hydrogen bonds, greatly influencing the structure and functions of biomacromolecules or compromising electronic properties such as charge transport (12)(13)(14)(15). Indeed, anhydrous TLC systems containing glycolipids (16)(17)(18)(19), ferritin (20), and polylysine have been reported (21)(22)(23).…”
mentioning
confidence: 99%
“…It is widely accepted now that long‐range charge transport in DNA occurs primarily via a multistep hopping mechanism in which guanine base pairs function as carriers of the positive charge (Giese, 2002). Conflicting interpretations about the nature of DNA conductivity have been linked to the sensitivity of transport measurements to the purity of the samples, intrinsic properties of the DNA molecule (such as conformation and length), and extrinsic parameters that modulate these properties (e.g., humidity) (Yamahata et al ., 2008). Evidence is also emerging in support for a mechanism of GS T4P conductance dominated by multistep hopping (Feliciano et al ., 2015).…”
Section: Geobacter T4p: a Paradigm In Structure And Functionmentioning
confidence: 99%